Strategi Efektifitas Digital Marketing untuk Meningkatkan Daya Saing UMKM Lokal - Aminuddin, Aminuddin; Ahmad Choiri (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2025)
This study explores the application of digital marketing strategies as a means to enhance the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in rural areas, particularly in light of the challenges posed by shifting market dynamics during the COVID-19 pandemic. Utilizing a descriptive qualitative approach, this research analyzes data derived from an extensive review of academic literature, including journals, articles, and relevant research reports, to identify best practices and provide a comprehensive overview of the utilization of social media and online marketplaces in marketing MSME products.The findings indicate that digital marketing serves a critical role in expanding market reach, fostering customer interactions, and optimizing business processes for MSMEs. However, the implementation of these strategies continues to face significant obstacles, such as low digital literacy among entrepreneurs, limited access to technology, and increasingly intense competition within the digital space. To address these challenges, the study recommends the development of targeted training programs and supportive policies that promote the digitalization of MSMEs, thus enhancing their long-term competitive viability.The insights derived from this research are expected to offer valuable guidance for MSME practitioners and policymakers as they navigate the path toward inclusive and sustainable digital transformation, ultimately contributing to robust economic growth and resilience in rural communities.